Estudo da influência de baixos teores de platina em catalisadores Ni/γ-Al2O3 nos processos de reforma a vapor, oxidação parcial e reforma oxidativa do metano - Dias, Joelmir Augusto Costa (2002)
The effect of platinum addition in low contents (0.1 and 0.3 % wt.) in nickel supported γ−alumina catalyst (15% Ni wt.) has been investigated. The samples were prepared by successive wet impregnations of metal ions over alumina and calcined at 600oC. X-Ray diffraction analysis showed that, structurally, platinum did not make sensitive changes in the catalyst precursor. No changes have been observed in textural properties, as shown by B.E.T. and pore-volume experiments. However, temperature programmed reduction showed that platinum facilitates the reduction of nickel during the activation step. According to the temperature programmed hydrogen desorption analysis, a sensitive increasing in metallic area and a decrease in metallic particles size were observed. The promotion effect of platinum in steam reforming, partial oxidation and the oxidative reforming reactions was related with the metallic area increase or the metallic particle size decrease, increasing the methane conversion with the increase in the metallic area in the case of steam and oxidative reforming, and decreasing the specific activity with the decrease in the metallic particle size, in the case of partial oxidation. Diffuse reflectance of infrared spectroscopy analysis of reduced samples showed that, in these low contents, the platinum do not influences significantly the carbon monoxide adsorption over nickel. This is evidence that there are no sensitive electronic changes in nickel sites by these low platinum contents. The hydrogen production per methane consumed for oxidative reforming of methane is the largest of these three processes, making this process the most advantageous for hydrogen generation for fuel cells.